Pengembangan Bahan Ajar Peserta Didik Berbasis Video Animasi Whiteboard Pada Materi Alat-Alat Optik Di SMA Negeri 2 Kupang Timur - Martha Radja; Egidius Dewa; Oktavianus Ama Ki`i (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
This study aims to produce whiteboard animation video-based student teaching materials on optical equipment material motivated by students who tend to be lazy to read printed books. The purpose of this study was to determine the validity and response of students to whiteboard animation video-based teaching materials on optical devices. The method in this research is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection instruments used teaching material validation sheets to determine the feasibility of teaching materials and student response sheets to find out students' responses to whiteboard animation video-based teaching materials on optical devices. Based on the results of data analysis by expert validation, the average result of all aspects of the assessment is 0.864 with a very feasible category. The results of implementation on students by giving a response of 93% with a very good category.